Arteriomegaly with synchronous true aneurysms; Management of Common Femoral Artery and Profunda Femoris Artery aneurysms in a 70-year-old male – A case report. (May 2022) - Yahya, Okab; Obaisy, Mohammad Mohannad; Al Laham, Omar; Ghannam, Mohammad; Mohammad, Ammar
Abstract: Introduction and importance: Arteriomegaly is characterized by an abnormal elastic defect of arterial vessels, which causes them to become elongated and tortuous. This raises the risk of limb loss due to thromboembolism, bleeding, infection, aneurysmal degeneration, dissection, or rupture. Despite asymptomatic presentations, surgical intervention could be warranted to plummet the morbidity and mortality associated with this pathology. Case presentation: We report the case of a 70-year-old male who presented with intermittent claudication in the left lower limb at a 100 m. Clinical examination revealed a pulsatile mass in the left groin with absent pulses in the left Popliteal and Pedal arteries. Radiology demonstrated a diffuse enlargement of the Abdominal Aorta with an infrarenal AAA, a L-CFA aneurysm, and a L-PFA aneurysm accompanied by occlusion of the L-SFA. Open surgical repair was achieved. Clinical discussion: Our patient was managed by arterial ligation and surgical excision of both concomitant aneurysms where we placed a Dacron graft from the L-CIA to the branch of the L-PFA whilst placing a supported ePTFE graft from the previously mentioned Dacron graft of the deep femoral branch to the left below-knee Popliteal Artery. Conclusion: Arteriomegaly is considered an exceptionally rare and progressive disease. Patients affected by this pathology have higher incidence rates of aneurysmal degeneration and even loss of the affected limb, especially if it's a peripheral aneurysm. Bypass surgical repair is feasible with positive outcomes, and it is prophylactic against the wide spectrum of dire consequences for patients. Highlights: Arteriomegaly is the vascular ectasia of arteries which may or may not be accompanied by aneurysms. Aneurysms are an abnormal expansion in the lumen diameter of arteries of 1.5 times the original diameter. The incidence of Arteriomegaly ranges from 1.6%–11% as an incidental finding in patients getting lower extremity imaging. FAAs are rare and constitute merely 3.1% out of the total number of arterial aneurysmal repair surgeries. Elective surgical repair of asymptomatic FAAs of a diameter larger than 25 mm is the gold standard.